2021
DOI: 10.1093/eurheartj/ehab637
|View full text |Cite
|
Sign up to set email alerts
|

Ciraparantag reverses the anticoagulant activity of apixaban and rivaroxaban in healthy elderly subjects

Abstract: Aims  Ciraparantag is a reversal agent for anticoagulants including direct oral anticoagulants. The aim was to evaluate the efficacy and safety of ciraparantag to reverse anticoagulation induced by apixaban or rivaroxaban in healthy elderly adults. Methods and results  Two randomized, placebo-controlled, dose-ranging trials conducted in healthy subjects aged 50–75 years. Subjects received apixaban (Study 1) 10 mg orally twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Thus, in a “real-world” study of a U.S. population, major bleedings on apixaban were almost 5% per year 12 and even higher, close to 8%, in a Korean population. 13 Furthermore, bleeding complications in apixaban-treated patients which require actions from health care may occur in up to one-third of treated patients per year, according to data from U.S. 12 On the other side, there are now effective antidotes approved 14 or under clinical evaluation 15 for the reversal of apixaban. Of note, andexanet alfa (AA) (coagulation factor Xa [FXa] [recombinant] inactivated-zhzo), a FXa decoy, has been approved for patients treated with a direct FXa inhibitor (apixaban or rivaroxaban) when reversal of anticoagulation is needed, due to life-threatening bleeding or uncontrolled bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in a “real-world” study of a U.S. population, major bleedings on apixaban were almost 5% per year 12 and even higher, close to 8%, in a Korean population. 13 Furthermore, bleeding complications in apixaban-treated patients which require actions from health care may occur in up to one-third of treated patients per year, according to data from U.S. 12 On the other side, there are now effective antidotes approved 14 or under clinical evaluation 15 for the reversal of apixaban. Of note, andexanet alfa (AA) (coagulation factor Xa [FXa] [recombinant] inactivated-zhzo), a FXa decoy, has been approved for patients treated with a direct FXa inhibitor (apixaban or rivaroxaban) when reversal of anticoagulation is needed, due to life-threatening bleeding or uncontrolled bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Ciraparantag (formerly PER977) also neutralizes the activity of heparin (see Section IV.B), and that of the DOACs, through charge-charge interactions, without affecting physiologic coagulation factors or the efficacy of other commonly used (nonanticoagulant) drugs (Ansell et al, 2022). Ciraparantag was found to reverse the effects of apixaban and rivaroxaban in a dose-related manner, in dose-ranging trials in healthy elderly subjects, and was well tolerated (Ansell et al, 2022;Chan and Weitz, 2022). Ciraparantag was also demonstrated to reverse the bleeding effects induced by UFH and a LMWH (enoxaparin) in a preclinical (rat) model, whereas protamine did not (Ansell et al, 2021).…”
Section: B Heparin In Relation To Alternative Anticoagulantsmentioning
confidence: 99%
“…However, protamine did restore the APTT to control levels whereas ciraparantag had no effect on this measurement, with similarly contradictory effects on an anti-FXa assay (Ansell et al, 2021;Siegal, 2021). Hence, standard plasma-based assays are not suitable tools to assess the effect of ciraparantag on anticoagulant reversal (Ansell et al, 2022), with whole-blood clotting time being used successfully for this purpose in animal and human studies (Ansell et al, 2014(Ansell et al, , 2016(Ansell et al, , 2021(Ansell et al, , 2022.…”
Section: B Heparin In Relation To Alternative Anticoagulantsmentioning
confidence: 99%
“…A follow-up substudy looked at healthy elderly subjects and found similar results where there was complete reversal of WBCT within 1hour post-ciraparantag and sustained up to 6 hours in a dosedependent manner. 193 A phase I study showed ciraparantag to induce full reversal of edoxaban within 10 minutes and sustained for 24 hours. 33 The aforementioned studies suggest that ciraparantag may be a safe and efficacious reversal agent for DOACs.…”
Section: Specific Antidotesmentioning
confidence: 99%